72.1k views
3 votes
⚠️ Show work for points ⚠️

Which expression is equivalent to the given expression? 5x-2


A. 2-5x.

B. 3-5 + 2x.

C. 5x – 2x.

D. 2x - 2 + 3x

User Praj
by
4.7k points

1 Answer

3 votes

Answer:

D

Explanation:

A is not, because 2-5x = -5x+2

(nothing has changed but the order)

B is not, because 3-5+2x = 2x-2

because 3-5 = -2. so -2+2x can be rewritten as 2x-2.

C is not, because 5x-2x = 3x

because you combine like terms, and 5-2 is 3

D is, because 2x-2+3x = 5x-2

because you combine like terms (2x+3x=5x) and -2 is left.

User Boaz
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.